Rainfall Induced 137Cs Radioactivity in the Aegean Sea - Tsabaris, C.; Ballas, D.; Papadopoulos, C. T.; Vlastou, R.; Kalfas, C. A. (HNPS Advances in Nuclear Physics, 2020)
The development of autonomous measuring systems for radioactivity in the ma- rine environment is today of important scientific priority for the marine sciences and especially for the Operational Oceanography. This paper concentrates on the improvement and application of an existing Nal-based gamma ray detection system for radioactivity measurements in seawater. The set up of the system will be described together with the appropriate calibrations in the laboratory. The operation of the system in the Aegean Sea provides the monitoring efficiency at 1461 keV by intercalibration with an appropriate salinity sensor mounted close to the Nal-detector. The gross counting rate was found constant within the statistical uncertainty of the measurements, during dry periods. The artificial radioactivity (137Cs) in the North Aegean Sea was increased, however, up to seven times after strong rainfall, compared to the mean radiation level as given in literature. This increment remains only for a short period of time (~2 days), due to strong advection processes of the water masses during strong rainfall.